2019
DOI: 10.1002/admi.201900970
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Strengthening and Toughening the Interphase of Composites by Constructing Alternating “Rigid‐and‐Soft” Structure on Carbon Fiber Surface

Abstract: strength, [7] while weakening the interphase can produce additional toughness via fiber debonding and plastic deformation of the interfacial layer. [8] Therefore, engineering the interphase so as to solve the conflict between strength and toughness affords a good opportunity.Nacre, a unique microscale architecture of "brick-and -mortar" that can reform after breaking, endows it with pre-eminent mechanical strength and toughness. [9] Thus, considerable attentions have been contributed to mimic this delicate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…After PDA modification, more characteristic function groups of PDA emerged, including the stretching of C-H in the benzene ring at 3018 cm −1 , the stretching vibration of indole ring at 1560 cm −1 and shearing vibration of aromatic C=N at 1390 cm −1 [ 25 , 26 ], suggesting the presence of PDA and a Schiff base reaction occurring on the fiber surface. The intensity of the peak at 2800–2980 cm −1 became higher, indicating the presence of a Michael reaction [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After PDA modification, more characteristic function groups of PDA emerged, including the stretching of C-H in the benzene ring at 3018 cm −1 , the stretching vibration of indole ring at 1560 cm −1 and shearing vibration of aromatic C=N at 1390 cm −1 [ 25 , 26 ], suggesting the presence of PDA and a Schiff base reaction occurring on the fiber surface. The intensity of the peak at 2800–2980 cm −1 became higher, indicating the presence of a Michael reaction [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The “rigid-flexible” architectures inspired by the nacre have drawn a lot of attentions because it can endow composites with prominent mechanical strength and toughness [ 13 ]. Inorganic nanoparticles are usually selected as “rigid” components to incorporate in the interface for improving mechanical strength, such as graphene, nanoclay, carbon nanotube (CNT) and TiO 2 [ 14 , 15 , 16 , 17 ]. Nevertheless, in most cases, nanoparticles need to be pretreated in order to introduce active sites to increase the interaction with carbon fiber and matrix resin.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffened modulus intermediate layer formed by TAPc would increase the cross-linking density of the interphase and shield crack propagation from touching the fiber surface, whereas the constrained plastic deformation of the interphase limited the release of thermal residual stresses during curing and the efficiency of crack blunting. On the other hand, the flexible interphase formed using a ductile polymeric material would act as macromolecular coupling agents between the fiber and matrix, which improves the potential energy-absorbing capacity but reduces the adhesion force between the CF and resin matrix . In view of the design of the interfacial structure with both high stiffness and suitable toughness, the rigid-and-flexible interphase with rigid/soft structures was proposed as a prospective strategy, among which the rigid component served as the robust shielding layer to deflect the crack path and the soft component acted as a stress-relief medium by inducing viscoplastic energy dissipation. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the rigid-and-flexible interphase was constructed by block or branched copolymers consisting of π-conjugate organic molecules (rigid component) bonded covalently by polymer chains (soft component). ,, According to the work of Deng et al, a diblock copolymer hydroxyl-terminated poly­( n -butylacrylate)- b -poly­(glycidyl methacrylate) (HO-PnBA- b -PGMA) was synthesized by atom-transfer radical polymerization (ATRP) and introduced into the interphase between the CF and epoxy resin, proving that the length of the PGMA block had a great influence on the interfacial properties of the CF composite . PGMA and poly (styrene- co -maleic anhydride)-grafted multiwalled carbon nanotubes were spray-coated onto the surface of CF fabrics by Yao et al, which established the interphase consisting of the PGMA soft component to provide stress dissipation accompanied by stable fiber slippage .…”
Section: Introductionmentioning
confidence: 99%
“…[10,12] Recent studies have shown the capability of developing functional materials through the incorporation of thin films on reinforcing agents' surface by using the layer-by-layer (LBL) deposition method. [13][14][15][16] In this work, polypropylene composites with hybrid interface were produced by alternatively depositing two polymers on the glass fiber (GF) surface, poly(diallyldimethylammonium chloride) (PDDA) and poly (sodium 4-styrenesulfonate) (PSS) containing oxidized multiwalled carbon nanotubes (MWCNT-COOH), via the LBL method. [16,17] For obtaining a clear description of the influence of the designed interface on the mechanisms of energy relief during crack propagation, in situ tensile tests were monitored by phase-contrast tomography (PCT) using synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%